Age Differences in Cardiopulmonary Exercise Testing Parameters in Heart Failure with Reduced Ejection Fraction - Garcia Brás, Pedro (2023)
Background and Objectives: Cardiopulmonary exercise testing (CPET) is a cornerstone of risk stratification in heart failure with reduced ejection fraction (HFrEF). However, there is a paucity of evidence on its predictive power in older patients. The aim of this study was to evaluate the prognostic power of current heart transplantation (HTx) listing criteria in HFrEF stratified according to age groups. Materials and Methods: Consecutive patients with HFrEF undergoing CPET between 2009 and 2018 were followed-up for cardiac death and urgent HTx. Results: CPET was performed in 458 patients with HFrEF. The composite endpoint occurred in 16.8% of patients ≤50 years vs. 14.1% of patients ≥50 years in a 36-month follow-up. Peak VO2 (pVO2), VE/VCO2 slope and percentage of predicted pVO2 were strong independent predictors of outcomes. The International Society for Heart and Lung Transplantation thresholds of pVO2 ≤ 12 mL/kg/min (≤14 if intolerant to β-blockers), VE/VCO2 slope > 35 and percentage of predicted pVO2 ≤ 50% presented a higher overall diagnostic effectiveness in younger patients (≤50 years). Specific thresholds for each age subgroup outperformed the traditional cut-offs. Conclusions: Personalized age-specific thresholds may contribute to an accurate risk stratification in HFrEF. Further studies are needed to address the gap in evidence between younger and older patients.